2016
DOI: 10.5213/inj.1630432.216
|View full text |Cite
|
Sign up to set email alerts
|

Association of Functional Ability and Benign Prostatic Hyperplasia With Urinary Incontinence in Older Korean Men

Abstract: Purpose:The purpose of this study was to determine the prevalence of urinary incontinence (UI) and analyze its association with instrumental activities of daily living (IADL) and benign prostatic hyperplasia (BPH) in community-dwelling older men in Korea.Methods:This study was a secondary analysis of data from the Actual Living Condition of the Elderly and Welfare Need Survey conducted in the year 2008. Data was subjected to hierarchical logistic regression analysis to examine the association of IADL and BPH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
2
8
0
5
Order By: Relevance
“…The self-reported prevalence of UI by the elderly was 36.3% in women and 17.0% in men in a study carried out in Florianópolis (Santa Catarina) 8 , 26.2% in women and 11.8% in men in São Paulo (São Paulo) 6 , 69.5% in women and 30.5% in men in Uberaba (Minas Gerais) 10 , and 31.1% in women and 23.2% in men in Montes Claros (Minas Gerais) 17 . In a study in Korea with people 60 years of age or older, UI was reported in 6.5% of women 15 and 3.9% of men 18 . And in the USA, in a study with women and men aged 50 years or older, the prevalence of UI was 19.8 and 6.4%, respectively 7 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The self-reported prevalence of UI by the elderly was 36.3% in women and 17.0% in men in a study carried out in Florianópolis (Santa Catarina) 8 , 26.2% in women and 11.8% in men in São Paulo (São Paulo) 6 , 69.5% in women and 30.5% in men in Uberaba (Minas Gerais) 10 , and 31.1% in women and 23.2% in men in Montes Claros (Minas Gerais) 17 . In a study in Korea with people 60 years of age or older, UI was reported in 6.5% of women 15 and 3.9% of men 18 . And in the USA, in a study with women and men aged 50 years or older, the prevalence of UI was 19.8 and 6.4%, respectively 7 .…”
Section: Discussionmentioning
confidence: 95%
“…This variability can also be explained by the adoption of different definitions for UI or even different methodologies 6 . It can also be attributed to cultural differences between regions in how UI is perceived by older adults 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, o diagnóstico que determina o tipo de IU, que o individuo apresenta, pode ser difícil de ser estabelecido em alguns casos. Portanto para a investigação dessa condição, utilizam-se os seguintes recursos: anamnese, questionários de qualidade de vida, diário urinário, pad test, exame físico, estudo urodinâmico, sendo que este último pode permitir diagnóstico preciso (PARK & HONG, 2016). No presente estudo, apenas foi realizada a anamnese, pois é de fácil aplicabilidade.…”
Section: Resultsunclassified
“…Entretanto, essa definição não leva em consideração a grande variação desse sintoma e a interferência causada na vida dos indivíduos incontinentes (ARAÚJO et al, 2015). A incontinência urinária (IU) pode ser classificada em quatro grupos: Incontinência Urinária de Esforço (IUE) definida como perda involuntária de urina ao esforço ou exercício, ou ao espirrar ou tossir; Incontinência Urinária de Urgência (IUU) sendo entendida como a perda involuntária de urina acompanhada, ou imediatamente precedida, por urgência de urinar; Incontinência Urinária Mista (IUM), disfunção que apresenta associação dos sintomas da IUE e IUU; e Incontinência Urinária Inconsciente (IUI) que é a perda de urina sem urgência ou reconhecimento consciente do extravasamento (CAVALCANTE et al, 2014;SUMARDI et al, 2016;PARK & HONG, 2016).…”
Section: Introductionunclassified